Аналіз потреби ТЕС України в енергетичному вугіллі з урахуванням вимог до якості палива - Perov M.O.; Makarov V.M.; Novytskyi I.Yu. (General Energy Institute of the National Academy of Sciences of Ukraine, 2016)
The thermal power industry of Ukraine is based on  14 large  power plants  working on coal. The boilers of seven plants were  designed to burn coal of the gas group and the other seven to work on anthracite fuel. The use of non-designed or low-grade fuel leads to a decrease in the efficiency of power units and an increase in fuel consumption accelerates the wear of furnace  equipment, and, in more severe cases, can cause accidents. In addition, the use of poor-quality coal increases the burden on the environment due to harmful emissions. In view of these facts, the problem of satisfying the demand of our thermal power plants (TPP) for coal of  the specified quality  is now  extremely urgent.In this paper, we analyze the current state of the Ukrainian thermal power industry and general zed  technical-and-economic characteristics of the domestic power units in comparison with foreign. This analysis shows that such parameters as efficiency, specific fuel consumption, etc. lag behind not only  European, but even  domestic achievements in 1975–1980. We revealed the shortcomings of price formation at the market of domestic coal, which make it low- competitive as compared with imported and require their removal for improving the situation.On the basis of these studies, we calculated the predictive volumes of finished coal products and the demand of TPP for coal with regard for the volume of electricity production for three scenarios of possible development of the coal industry: optimistic, basic, and pessimistic. Calculations show that the demand of TPP  for coal production according to the optimistic scenario is satisfied with the participation of mines situated  within performing ATO. By the basic scenario, there is a shortage of coal production about 19–20 million tons. According to the pessimistic scenario, the demand exceeds production by 19.9  and 15.8 million tons in 2020 and 2030, respectively.